2011
DOI: 10.5657/fas.2011.0192
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Polyphenol Content and Antioxidant Activity of Brown Alga Eisenia bicyclis Extract by Microbial Fermentation

Abstract: The objective of this study was to select an effective microbial strain to improve the functional qualities of Eisenia bicyclis water extract by fermentation. For this purpose, several microorganisms isolated from traditional Korean fermented foods were inoculated and cultivated in E. bicyclis water extract. Ultimately, yeast strain YM-1 was selected for further study based on its total phenolic compound (TP) content and antioxidant activity, which were enhanced by microbial fermentation. The extract fermented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
23
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 29 publications
2
23
0
Order By: Relevance
“…2) and the highest phenolic content was found after 5 days of fermentation. These results are consistent with the previous data showing that Lactobacillus fermentation of a Hizikia fusiforme [32] and yeast fermentation of Eisenia bicycilis [30] enhanced the phenolic content. The enhancement of phenolic content might be due to the fact that enzymes released from A. oryzae breakdown the cell wall of seaweed which helps to release out more phenolic compounds in the water.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…2) and the highest phenolic content was found after 5 days of fermentation. These results are consistent with the previous data showing that Lactobacillus fermentation of a Hizikia fusiforme [32] and yeast fermentation of Eisenia bicycilis [30] enhanced the phenolic content. The enhancement of phenolic content might be due to the fact that enzymes released from A. oryzae breakdown the cell wall of seaweed which helps to release out more phenolic compounds in the water.…”
Section: Discussionsupporting
confidence: 83%
“…Recently, fermentation of seaweed has been attracting much more interest as seaweed contains lots of polysaccharides. Previously, it has been reported that fermentation of seaweed by different lactic acid bacteria enhances the bioactive compound as well as biofunctional activity [27][28][29][30]. However, submerged fermentation of S. japonica by A. oryzae has been merely reported.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In fact, compounds with antioxidant, antiviral, antifungal, and antimicrobial activities have been detected in brown, red, and green algae (Eom et al, 2011). Ecklonia cava, of the family Laminariaceae, ranges along the eastern coast of Korea and Japan.…”
Section: Disk Diffusion Assaymentioning
confidence: 99%
“…The antibacterial efficacy of marine algae extracts was evaluated by disk diffu sion assay followed by the CLSI (2009), as described in our previous reports (Lee et al, 2014;Eom et al, 2011). In brief, bacterial strains were cultured in BHI at 37°C until an OD at 600 nm of 0.5.…”
Section: Disk Diffusion Assaymentioning
confidence: 99%